Facial miliary osteoma in HIV patient Osteoma miliar da face em paciente portadora do HIV - Camila Camozzato; Franciani de Oliveira Basso; Rodrigo Pereira Duquia; Ana Letícia Boff; Hiram Larangeira de Almeida Jr (Sociedade Brasileira de Dermatologia, 2011)
Facial miliary osteoma is characterized by the presence of multiple normochromic papules, affecting mainly middle-aged women, with a previous history of acne. A 39-year-old HIV positive female patient presented hardened papules which had appeared 3 years before, located on the malar region, glabella and mentum. Optical microscopy showed spherical bone formations in the dermis. Computerized tomography of the face revealed small calcifications on the surface consistent with bone formation. Multiple facial osteomas are rare as well as its association with HIV virus infection Os osteomas miliares da face são caracterizados por múltiplas pápulas normocrômicas na face, afetando, geralmente, mulheres de meia idade, com história pregressa de acne. Uma paciente de 39 anos, portadora do HIV, apresentou pápulas endurecidas, com 3 anos de evolução, localizadas na região malar, glabela e mento. A microscopia óptica demonstrou formações ósseas esféricas na derme. A tomografia computadorizada da face observou pequenas calcificações na superfície, compatíveis com formação óssea. Os osteomas múltiplos da face são raros assim como sua associação com a infecção pelo HIV